MICRONUCLEUS ASSAY - SCREENING TOOL IN THE DIAGNOSIS OF ORAL CARCINOMA IN TOBACCO USERS - N PRATHEEPA SIVASANKARI,; S KAUR,; K.S REDDY,; K RAMACHANDRA RAO,; S.J. MADHAN KUMAR, (International Journal of Pharma and Bio Sciences, 2012)
Cancer is one of the most important non communicable diseases with high mortality rate. Cancer of the oral cavity is common in south Indian male population due to the usage of tobacco in the form of cigarette smoking and smokeless tobacco. The genotoxic risks in tobacco users on buccal mucosa can be assessed by Micronucleus (MN) test. 25 patients with oral carcinoma and 25 patients with various pre malignant diseases were included in our study. They were screened for micronucleus. MN frequency was significant (p<0.001) among tobacco users than non users in the cancer group and the MN frequency were not significant among the pre malignant tobacco users , so the present study can be used as a screening test in the population using tobacco.